To solve for v, we will distribute and simplify both sides of the equation.
Starting with the left side:
4v + 8 - 2(-6v - 2)
= 4v + 8 + 12v + 4
= (4v + 12v) + (8 + 4)
= 16v + 12
Now, simplifying the right side:
4(v - 1)
= 4v - 4
Setting the left side equal to the right side:
16v + 12 = 4v - 4
To solve the equation, we will isolate v on one side of the equation.
Subtracting 4v from both sides:
16v - 4v + 12 = -4
Combining like terms:
12v + 12 = -4
Subtracting 12 from both sides:
12v = -4 - 12
12v = -16
Finally, dividing both sides by 12:
v = -16/12
v = -4/3
Therefore, v = -4/3.
solve for v
4v+8-2(-6v-2) = 4(v-1)
1 answer